Tumor-Intrinsic Mechanisms Regulating Immune Exclusion in Liver Cancers - Lindblad, Katherine E.; Ruiz de Galarreta, Marina; Lujambio, Amaia (Frontiers in Immunology, 2021)
Representing the fourth leading cause of cancer-related mortality worldwide, liver cancers constitute a major global health concern. Hepatocellular carcinoma (HCC), the most frequent type of liver cancer, is associated with dismal survival outcomes and has traditionally had few treatment options available. In fact, up until 2017, treatment options for advanced HCC were restricted to the broad-acting tyrosine kinase inhibitor Sorafenib, which was the standard of care. Since 2017, a multitude of mono- and combination immunotherapies that include pembrolizumab, nivolumab, ipilumumab, atezolizumab, and bevacizumab have been FDA-approved for the treatment of advanced HCC with unprecedented response rates ranging from 20-30% of patients. However, this also means that ~70% of patients do not respond to this treatment and currently very little is known regarding mechanisms of action of these immunotherapies as well as predictors of response to facilitate patient stratification. In order to understand how immunotherapies work in the context of HCC and establish biomarkers of response and resistance, mechanisms of immune surveillance and immune escape in the context of HCC must be elucidated. The aim of this review is to summarize the current knowledge to date of tumor-intrinsic mechanisms of immune escape in liver cancer, specifically in the context of HCC.